Research on Soil Anti-scourability in Karst Area Based on Artificial Simulated Rainfall and Undisturbed Soil Scouring Experiment - WEI Xiaocha; LONG Xiaomei; TANG Xin; LIU Yang; XIAO Yang; LI Hongguang (Renmin Zhujiang)
Soil anti-scourability is of great significance for soil and water conservation and ecological environment construction in Karst area. Taking the soils in broad-leaved forest, coniferous forest and shrub-grass land as the research objects, this paper researches the dynamic variation characteristics of soil anti-scourability and its influencing factors under different vegetation types in karst area by the artificial simulated rainfall and undisturbed soil scouring experiment. The results show that: (1) Within 2 min of rainfall scouring, the sediment yield of soil in different vegetation types is especially large, then gradually decreases, and reaches a stable state after 9 min. In general, the sediment yield of shrub-grass land was largest, followed by coniferous forest and broad-leaved forest, and the sediment yield of different vegetation types increases gradually with the increase of the slope. (2) The soil anti-scourability of shrub-grass land is lowest at the slope of 15°, which is obvious different from the broad-leaved and coniferous forest, but in the slope of 45°and within 4~12 min of rainfall scouring, the soil anti-scourability of broad-leaved forest is the strongest, followed by shrub-grass land and coniferous forest. Soil anti-scourability of different vegetation types are different, that is broad-leaved forest >coniferous forest >shrub-grass land. With strongest soil anti-scourability, the broad-leaved forest is beneficial to soil and water conservation. (3) The soil anti-scourability of different vegetation types increases gradually with the increase of the rainfall scouring time, and the slope and root system, especially the root of vegetation with more than 1 mm diameter, have important influences on the soil anti-scourability.